Pagbabalik sa tribo (The Probe Team, 1999)
When Auraeus Solito discovers that he is a member of the Pala'wan tribe he return to his native land to begin a journey of self-discovery and the recovery of his tribe's history. This documentary also shows the problems that the tribe faces, including poverty, discrimination and the illegal grabbing of their ancestral domain.